ANALISIS MATERI GOTONG ROYONG PADA PEMBELAJARAN PKN DI UPT SPF SD NEGERI 106184 SEKIP - Fajrina, Fildzah Putri; Gulo, Seleksi Niat Three; Simanullang, Patricia; Rahmawati, Siska; Br Siagian, Erika Elisabet (Universitas Negeri Medan, 2024)
The importance of mutual cooperation in school life, there needs to be an attitude of mutual assistance between students and other students, and there also needs to be an attitude of mutual cooperation between students and teachers. Where this attitude of mutual cooperation also has Pancasila values in it, so this attitude of mutual cooperation must be encouraged in the life of the school environment. The study used a qualitative descriptive method in the process of collecting data. The stages carried out starting from observation, interviews, case studies and data analysis. Based on the results that have been presented, we can discuss that mutual cooperation has a significant positive impact on PKN learning in elementary schools. Instilling the value of mutual cooperation from an early age to elementary school children in schools has an important role in shaping their character and social skills. Mutual cooperation is not just an activity to clean the school environment, but also a means to foster a sense of responsibility, empathy, concern, cooperation, and respect for others. Keywords: mutual cooperation, elementary school, citizenship education